Análisis pragmático de dos expresiones de cortesía del español de Costa Rica y su adquisición por parte de estudiantes de español como segunda lengua - Urbina Vargas, Soledad (2004)
This article proposes the analysis, within the field of the pragmatic acquisition of a second language and specifically within the field of the development of strategies of politeness strategies and identification of speech acts, of two phrases "un día de estos lIegáte a mi casa" and "un día de estos hagamos algo". The investigation will show contrast between the perception and the identification of these phrases under study as a specific speech act, in native speakers and Spanish L2 leamers.